Vocational education and training in the field of social economy: A comparative analysis between five EU countries - Apostolopoulos, Nikolaos; Goulas, Christos; Koukouris, Alexandros; Papageorgiou, Ira (Adult Education Critical Issues, 2021)
This article is a combination of policy and research as, based on primary data, it develops the situation of Vocational Education and Training (VET) for Social Solidarity Economy (SSE) and explores the relevant educational programmes as a basic support mechanism of SSE in the EU. Moreover, this article shows that the connection between adult education and SSE is not accidental, but is based on converging principles of these two fields, and especially on their common mission regarding society transformation. The empirical data of the research comes from five countries (France, Greece, Italy, Croatia and the Czech Republic) which participate in an Erasmus+ programme coordinated by INE GSEE. This policy text comes to fill a gap in the literature of European SSE, given its limited exploration in general, and in particular in relation to VET. The importance of this article is even greater in view of the ongoing socio-economic crises (e.g. financial, health, environmental crisis), which highlight the fact that the SSE prospects can no longer be absent from the political agenda.